SEM evaluation of gap at the resin dentin interface in Class II composite resin restoration: an in vitro study - Mazumdar, P; Das, U Kumar; Kundu, R (Health Renaissance, 2012)
Introduction: Composite resins have become one of the most commonly used direct restorative materials for anterior and posterior teeth. Objectives: To observe and analyze the gap at the resin dentin interface in class II cavities restored with light cure composite resin in four experimental groups employing 37% phosphoric acid or self etching monomers and restored with /without light cure flowable composite resin. Methods: 40 sound maxillary first premolars, extracted due to orthodontic reasons was taken, distoproximal cavities were prepared and divided into 4 groups. Teeth of Group 1 was etched by 37% Phosphoric acid and light cure flowable composite resin was used, in group 2 ,two coats of self etching acidic monomer were applied and light cure flowable composite resin was used. Teeth of group 3 was etched with 37% phosphoric acid and restored without light cure flowable composite resin and in group 4, two coats of self etching acidic monomer were applied and restored without using light cure flowable composite resin material. Thermocycling was done after finishing and polishing and viewed under scanning electron microscope to observe and analyze the gap between tooth and the restoration. Result: Gap was observed at dentin-composite resin interface in all 4 groups. Results were evaluated by F-test and Manwhitney U test. No statistically significant difference was found. Conclusion: Use of flowable composite resin liner and the etching technique do not have any influence on the gap. DOI: http://dx.doi.org/10.3126/hren.v10i2.6571 Health Renaissance 2012; Vol 10 (No.2); 98-104